Glucocorticoid receptor response and glucocorticoid-induced leucine zipper expression in neutrophils of critically ill patients with traumatic and non-traumatic brain injury - Lotsios, N.S.; Vrettou, C.S.; Poupouzas, G.; Chalioti, A.; Keskinidou, C.; Pratikaki, M.; Giannopoulou, V.; Kotanidou, A.; Vassiliadi, D.A.; Dimopoulou, Ioanna; Vassiliou, A.G. (Frontiers in Endocrinology, 2024)
Objective: Critically ill patients, including those with brain injuries (BI) are frequently hospitalised in an intensive care unit (ICU). As with other critical states, an adequate stress response is essential for survival. Research on the hypothalamic-pituitary-adrenal gland axis function in BI has primarily focused on assessing ACTH and cortisol levels. However, the immunological, metabolic, and hemodynamic effects of glucocorticoids (GCs) are mediated through the glucocorticoid receptor (GCR), a ubiquitously distributed intracellular receptor protein. Data on GCR-α expression and its signalling in acute BI injury are lacking. Methods: We designed a prospective observational study, carried out in one academic multi-disciplinary ICU. Forty-two critically ill patients with acute (BI). These patients suffered from traumatic BI (N= 20), subarachnoid hemorrhage (N= 12), intracranial hemorrhage (N= 7), or ischemic stroke (N= 3). All patients were steroid-free. Twenty-four age and sex-matched healthy controls were used for comparison. Results: Expression of GCR-α and the glucocorticoid-inducible leucine zipper (GILZ), serum cortisol, interleukins (IL) 6, 8, 10 and TNF-α, and the BI biomarkers GFAP and total Tau were measured on ICU admission (within 48 hours) and 5-7 days from admission. Compared to healthy controls, in the critically ill patients with BI, GCR-α mRNA expression was significantly downregulated on admission, and after 5-7 days in the ICU (2.3fold, p<0.01, respectively). Even though GCR-α was downregulated, its downstream gene, GILZ, was expressed at the same levels as in normal controls on admission and was significantly upregulated 5-7 days following admission (2-fold, p<0.001). TNF-α levels were undetectable at both time-points. GCR-α expression levels inversely correlated with IL-6. The levels of cortisol and the BI biomarkers did not differ between the 2 time-points. Conclusions: We provide novel evidence on the downregulated expression and upregulated signalling of the ligand-binding and functionally active GCR-α isoform in the polymorphonuclear neutrophils (PMNs) of critically ill patients with BI. The increased GILZ expression indicates an increased GC sensitivity in the PMNs of BI critically ill patients.